Notes on modernity, decolonialism and cultural agency in Latin America - Leetoy, Salvador (2016)
This article elaborates on how modernity is appropriated in Latin America in terms of its own decolonial disposition. Accordingly, it is reviewed to what extent cultural agency strategies are constitutive of a transgressive construction of a modernity from below. It is stated that the Latin American condition cannot be considered just as a mere ideological pastiche of discourses of premodernity, modernity and postmodernity, since such a view is buttressed on Eurocentric reductionisms. Hence, it is established that a contextual perspective of historical, political and social conditions is needed in order to understand our particular subaltern condition.